Effect of Immediate Versus Delayed Pushing on Rates of Spontaneous Vaginal Delivery Among Nulliparous Women Receiving Neuraxial Analgesia: A Randomized Clinical Trial. Issue 3 (September 2019) - Cahill, A.G.; Srinivas, S.K.; Tita, A.T.N.; Caughey, A.B.; Richter, H.E.; Gregory, W.T.; Liu, J.; Woolfolk, C.; Weinstein, D.L.; Mathur, A.M.; Macones, G.A.; Tuuli, M.G.
Abstract : ( JAMA . 2018;320(14):1444–1454) Although >3 million women give birth in the United States every year, there is a lack of evidence regarding optimal labor management. In an effort to optimize cesarean delivery rates, there has been extensive research examining the management of labor. There are conflicting data on whether the mother should push immediately or delay pushing, as prolonged labor is associated with adverse outcomes for both mother and infant. The objective of this study was to evaluate whether immediate or delayed pushing would impact rates of spontaneous vaginal delivery as well as be more effective to reduce maternal and neonatal morbidities.